Combined Genetic Deletion of IL (Interleukin)-4, IL-5, IL-9, and IL-13 Does Not Affect Ischemic Brain Injury in Mice. Issue 8 (August 2019) - Perego, Carlo; Fumagalli, Stefano; Miteva, Kapka; Kallikourdis, Marinos; De Simoni, Maria-Grazia
Abstract : Background and Purpose—: After ischemic injury, microglia and infiltrated macrophages may acquire different polarization phenotypes promoting inflammation and injury (M1) or repair and protection (M2). There is evidence that immunomodulation, via type 2 helper T-cells (Th2) cytokines, exerts neuroprotection after ischemia. We investigated the consequences of simultaneous genetic deletion of Th2 cytokines (IL [interleukin]-4, IL-5, IL-9, IL-13) on the histopathologic outcome, microglia and infiltrated macrophages markers, and ischemic microenvironment at different time points after ischemic injury in mice subjected to permanent occlusion of the middle cerebral artery. Methods—: Wild-type and Th2 cytokine-deficient mice (4KO) were subjected to permanent occlusion of the middle cerebral artery by electrocoagulation and followed up to 5 weeks after permanent occlusion of the middle cerebral artery. Neuropathologic outcome was assessed at 24 hours (n=6), 7 days (n=6), and 5 weeks (n=6–7) by examination of the ischemic lesion, neuronal count, microglia and infiltrated macrophages markers, brain atrophy, collagen deposition, and GFAP (glial fibrillary acidic protein) immunohistochemistry. Selected gene expression was investigated at 7 days (n=6). Results—: 4KO mice showed no difference in lesion and neuronal count 7 days and up to 5 weeks after permanent occlusion of the middle cerebral artery compared with wild type. Ischemic 4KO mice had lower CD16/32 expression at 24 hours, lower CD11b and CD16/32 expression at 7 days than wild type. They had higher CD206 expression at 24 hours, higher CD206 and arginase1 at 7 days, and increased mRNA for CXCL9 (chemokine [C-X-C motif] ligand 9) compared with wild type. Additional histopathologic analysis, including brain atrophy, gliotic scar, and collagenous scar confirmed no difference between genotypes at 5 weeks. Conclusions—: This study casts light on the proposed neuroprotective function of Th2 cytokines, showing that combined IL-4, IL-5, IL-9, IL-13 deletion does not affect the neuropathologic response to ischemic stroke in the subacute and chronic phases. Our findings indicate that Th2 cytokines are not an essential neuroimmunological cue able to drive the brain's ischemic outcome. Abstract : Supplemental Digital Content is available in the text.